2001
DOI: 10.1007/s11745-001-0713-9
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral differential leukocyte counts in humans vary with hyperlipidemia, smoking, and body mass index

Abstract: Reports of diverse relationships between blood concentrations of different lipids and peripheral total leukocyte count, and a unique lower peripheral monocyte count in hypercholesterolemia, have driven us to think that in humans, peripheral differential leukocyte counts may be influenced differently by different types of hyperlipidemia. Our subjects were Taipei residents who attended a regular health check program in our hospital in 1998. A total of 3,282 subjects was enrolled, including 1,677 normolipidemic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
40
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 27 publications
5
40
0
1
Order By: Relevance
“…Unlike other studies, we adjusted not only for age, smoking and drinking status, but also for a previous medical history of a disease associated with low-grade inflammation. Previous studies have mainly focused on associations between the WBC count and a single metabolic disorder such as diabetes, 26 hypertension 27,28 or hyperlipidemia, 29 but it may also be associated with several of these disorders, so we investigated possible associations between the WBC count and clusters of the 5 components of MS as defined in ATP III. We found that the average WBC count became significantly higher as the number of MS components increased, which suggests that subjects with a single MS component have low-grade inflammation, which intensifies as the number of MS components increases.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other studies, we adjusted not only for age, smoking and drinking status, but also for a previous medical history of a disease associated with low-grade inflammation. Previous studies have mainly focused on associations between the WBC count and a single metabolic disorder such as diabetes, 26 hypertension 27,28 or hyperlipidemia, 29 but it may also be associated with several of these disorders, so we investigated possible associations between the WBC count and clusters of the 5 components of MS as defined in ATP III. We found that the average WBC count became significantly higher as the number of MS components increased, which suggests that subjects with a single MS component have low-grade inflammation, which intensifies as the number of MS components increases.…”
Section: Discussionmentioning
confidence: 99%
“…1 Leukocyte count is positively related to CVD incidence and mortality 2 as well as to traditional cardiovascular risk factors, such as smoking, hyperlipidemia, and insulin resistance. 3,4 Triglycerides (TG) and glucose are able to induce leukocyte activation, as has been shown in vitro 5,6 and ex vivo in hypertriglyceridemic patients. 7 Neutrophil counts increase postprandially in healthy subjects, in CVD patients and in type 2 diabetics when TG and glucose rise.…”
mentioning
confidence: 89%
“…To determine whether monocyte mobilization in response to inflammatory insults also requires CCR2, we fed the mice a high-fat, high-cholesterol diet for 3.5 weeks to induce hypercholesterolemia, which leads to reproducible monocyte/ macrophage accumulation in blood vessel walls and inflammation (23,24). Others have reported an increase in the blood monocyte count in both mice (25) and humans (26) in response to chronic consumption of a high-fat diet. We found monocytosis in the 7/4 bri and 7/4 dim populations in WT mice, but not in the CCR2 -/-mice.…”
Section: Figurementioning
confidence: 99%